2020
DOI: 10.1155/2020/5431046
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Dye by Waste Black Tea Powder: Parameters, Kinetic, Equilibrium, and Thermodynamic Studies

Abstract: Waste black tea powder was used as a potential adsorbent to remove methylene blue (MB) from aqueous solution. Several operating factors in adsorption of MB onto waste black tea powder were investigated, including contact time, initial MB concentration, solution pH, adsorption temperature, and dosage of waste black tea powder. Experimental results revealed that the adsorption efficiency increased with contact time and solution pH values and decreased with initial MB concentration and adsorption temperature. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 42 publications
(38 reference statements)
3
40
1
Order By: Relevance
“…This trend is consistent with the findings of other researchers 26 , 69 , 70 . Thus as the BRB concentration in the aqueous phase increased, more BRB molecules were fixed on the active sites of ZnONPs 71 , which resulted in site saturation, surface repulsions, and less percentage removal of dye from solution 72 . The BRB concentration of 50 mg/L was selected for the batch experiments due to the associated optimum adsorption capacity, which indicated effective utilization of the actives sites of the as-prepared ZnONPs.…”
Section: Resultsmentioning
confidence: 99%
“…This trend is consistent with the findings of other researchers 26 , 69 , 70 . Thus as the BRB concentration in the aqueous phase increased, more BRB molecules were fixed on the active sites of ZnONPs 71 , which resulted in site saturation, surface repulsions, and less percentage removal of dye from solution 72 . The BRB concentration of 50 mg/L was selected for the batch experiments due to the associated optimum adsorption capacity, which indicated effective utilization of the actives sites of the as-prepared ZnONPs.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, adsorption is a very effective and attractive technique with respect to cost, ease of use, and simplicity [1][2][3]. Several studies have reported the use of low-cost materials for dye removal [15,16]. Various biosorbents such as Carica papaya [17], lotus leaf [18], olive stone [19], spent rice biomass [20], maize husk leaf [21], palm oil agrowaste [22], and pulverized marula seed husk [1] have been studied for sorption of methylene blue.…”
Section: Introductionmentioning
confidence: 99%
“…The pseudo-secondorder model explains the relationship between biosorbent and dyes through the sharing mechanism of the force of values or electrons, and assumes that chemisorption is the adsorption process and the rate-limiting step for the resulting reaction. 42 In order to study the behaviour of MB and MG adsorption kinetics for the nTiO 2 -Composite, pseudo-first-order and pseudo-second-order models were applied to kinetic studies (Fig. 8).…”
Section: Adsorption Kineticsmentioning
confidence: 99%